Prediction of the Factors Influencing the Shengjing Classification of Portal Vein Thrombosis after Splenectomy for Portal Hypertension in Cirrhosis: A Single-Center Retrospective Case-Control Study. (7th September 2020) - Song, Zimin; Feng, Hanxin; Yang, Chunbo; Dai, Chaoliu
Abstract : Objective . To compare the survival time of patients with portal vein thrombosis after splenectomy for portal hypertension in cirrhosis and explore the influencing factors of the Shengjing classification. Methods . Clinical data of 108 patients with portal vein thrombosis after splenectomy in the department of general surgery of our hospital from November 2011 to December 2018 were selected, and a retrospective analysis was performed. Results . Among 108 patients with postoperative PVST formation, 9 had type Ia, 32 type Ib, 39 type IIa, 20 type IIb, 5 type IIIa, 3 type IIIb, and 0 type IV. Survival analysis showed that the difference in survival time distribution among the Shengjing typing groups was statistically significant (P < 0.05 ). The higher the classification level, the shorter the survival time and the higher the risk of death. The results of a single-factor analysis showed that there were statistically significant differences in the PVST Shengjing typing groups between the preoperative group with or without hepatitis, preoperative d-dimer level, and postoperative day 14 fibrinogen (FIB) level (P < 0.05 ). Multivariate logistic regression analysis showed that the OR value of higher PVST Shengjing typing in patients with hepatitis was 4.634 times higher than that in patients without hepatitis (95% CI: 1.593-13.478, χ 2 = 7.922, P = 0.005 < 0.05 ). Preoperative d-dimer volume increased by 1  μ g/L; the OR value of higher grade PVST Shengjing typing was 1.001 times higher (95% CI: 1.000-1.002) than that of lower grade PVST Shengjing typing (χ 2 = 8.369, P = 0.004 < 0.05 ). Conclusions . The survival time of patients with portal vein system thrombosis after splenectomy was significantly different among Shengjing typing groups, and the higher the classification level, the shorter the survival time and the higher the risk of death. In patients with portal hypertension in cirrhosis and PVST formation after splenectomy, if the preoperative d-dimer level is high or accompanied by hepatitis virus, the formation of PVST will involve a wide range, the disease is more serious, and the prognosis is also poor, so corresponding preventive measures should be taken to avoid the aggravation of PVST.